Graded empathy: a neuro-phenomenological hypothesis - Levy, Jonathan; Bader, Oren (Frontiers in psychiatry, 2020)
The neuroscience of empathy has enormously expanded in the past two decades, thereby making instrumental progress for the understanding of neural substrates involved in affective and cognitive aspects of empathy. Yet, these conclusions relied on ultra-simplified tasks resulting in the affective/cognitive dichotomy that was often modelled and over-emphasized in pathological, developmental and genetic studies of empathy. As such, the affective/cognitive model of empathy could not straightforwardly accommodate and explain the recent surge of neuroscience data obtained from studies employing naturalistic approaches and intergroup conditions. Inspired by phenomenological philosophy, this article paves the way for a new scientific perspective on empathy that breaks thorough the affective/cognitive dichotomy. Our neuro-phenomenological account leans on phenomenological analyses and can straightforwardly explain recent neuroscience data. It emphasizes the dynamic, subjective and piecemeal features of empathic experiences and unpicks the graded nature of empathy. The graded empathy hypothesis postulates that attending to others' expressions always facilitates empathy, but the parametric modulation in the levels of the empathic experience varies as a function of one's social interest in the observed other (e.g., intergroup factors). Drawing parallels to other domains that integrate neuroscience with phenomenology, we describe the potential of this graded framework in an era of real-life experimentation; this original perspective through the lenses of neuro-phenomenology can change the way empathy is considered.
Gesehen am 12.01.2021